Fiasco : the American military adventure in Iraq - Ricks, Thomas E. (New York : Penguin Press, 2006)
From the Washington Post's two-time Pulitzer-winning senior Pentagon reporter, the definitive military chronicle of the Iraq War-and a searing judgment of its gross strategic blindness-drawing on the accounts of senior military officers giving voice to their anger for the first time.
Includes bibliographical references (p. [441]-462) and index.
Keywords: Iraq War, 2003-2011; United States -- History, Military -- 21st century